Analisis Sifat Kimia Ultisol Setelah Pemberian Kompos Solid dan Fly Ash Batubara - Idwar; Nelvia; Irfandri; Lubis, Nursiani; Veronica, Stevany (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2025)
This study aimed to evaluate the effects of applying solid compost and coal fly ash on the improvement of Ultisol chemical properties and to determine the optimal dosage for its application. Ultisol, known for its high acidity, low organic matter content, and limited nutrient availability, requires specific amendments for optimization. The study was conducted using a factorial completely randomized design (CRD) with 12 treatment combinations: four levels of solid compost (0 t.ha-1, 2,5 t.ha-1, 5 t.ha-1 dan 7,5 t.ha-1) and three levels of fly ash (0 t.ha-1, 3 t.ha-1 and 6 t.ha-1), each with three replications. The soil that has been treated is incubated for two weeks, then the chemical properties of the soil are analyzed. The results showed that the combination of solid compost and fly ash significantly improved Ultisol chemical properties, including increasing soil pH, reducing Al-dd levels, and enhancing P-available, organic carbon (organic C), total nitrogen (total N), cation exchange capacity (CEC), and total potassium (total K). The combination of 7,5 t.ha-1 solid compost and 6 t.ha-1 fly ash provided the best results, achieving a soil pH of 5.15, an increase available P to 23.7 ppm, and a high CEC level. This combination effectively improved Ultisol quality, making it more supportive for plant growth.